Dimensi Komitmen Organisasional: Dampaknya Terhadap Perilaku Kerja Pada Organisasi Sektor Publik - Sambung, Roby (Jurnal Terapan Manajemen dan Bisnis, 2016)
The goal of to the research to examine and analyze three dimensions of organizational commitment from meyer and allen models on work behavior publik Servants. To this end, after reviewing the literature on Reviews These themes, a conceptual framework with three hypotheses is proposed. Reviews These hypotheses were tested on 41 students of Master of Science in Management program through regresion with reflective indicator using SmartPLS 2.0M3. The main results of this study are as follows: (1) affective commitment strongly influence employee behavior, (2) the continuance commitment strongly influence employee behavior, (3) normative commitment strongly influence employee behavior. From the three commitment of normative commitment is a variable that affects most on work behaviors.